Effect of ketogenic diet on alzheimer's disease to improve cognitive function: A literature review - Anjani Daniyil Khoiroh (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Alzheimer's is the most common cause of neurodegenerative dementia which is characterized by reduced cognitive function. Alzheimer's disease is a serious global problem because so far no effective treatment has been found to prevent it. Improving diet can be used as therapy to prevent cognitive decline. The ketogenic diet is one of the recommended therapies because it is neuroprotective.Purpose: To review several studies related to the effect of giving a ketogenic diet in improving cognitive function in people with Alzheimer's.Method: This study used the literature review method using the PRISMA protocol. Literature searches were conducted online, sourced from Scopus, Science Direct, PubMed, ProQuest, and SpringerLink databases by entering a number of relevant keywords. The key words are "ketogenic diet" AND "alzheimer's disease" AND "cognitive function" OR "improves cognition". The conditions for the inclusion of the reviewed articles are publications for the last five years (2018 - 2023), in English, open access, and include research articles or original articles. The feasibility of this study was assessed by applying the PICO framework, including the samples used were humans or experimental animals suffering from Alzheimer's, the sample received a ketogenic diet intervention.Results: Showed an effect of the ketogenic diet on cognitive function in Alzheimer's patients. There were four articles reviewed where all articles examined the effect of giving a ketogenic diet on cognitive function in Alzheimer's sufferers. The ketogenic diet is a high-fat, low-carb diet that promotes the process of ketogenesis. The resulting ketone bodies, such as acetoacetate and β-hydroxybutyrate can meet the energy needs of brain cells and improve memory performance. The chronic effect of giving a ketogenic diet has been shown to increase cognitive test scores. However, acute administration of the ketogenic diet is still not known with certainty.Conclusions: The chronic intervention of the ketogenic diet has a positive effect on improving the cognitive function of Alzheimer's sufferers. The ketogenic diet has been shown to be safe, feasible, and recommended as a treatment method for Alzheimer's patients.